2016
DOI: 10.5194/aab-59-139-2016
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and cortisol patterns and the effects of electro-ejaculation and copulation in Awassi rams

Abstract: Abstract. The effects of month, electro-ejaculation (EE) and copulation process on testosterone and cortisol levels were investigated in Syrian Awassi rams. Jugular blood samples were collected from 10 rams at weekly intervals for 1 year. During the breeding and non-breeding season, samples were collected 60 min before EE and copulation as well as 0 (at the time of ejaculation), 20 and 60 min after EE and copulation. Low testosterone levels were detected from October to February (4.58-5.06 nmol L −1 ), while h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Testosterone secretion in small ruminants was driven by natural day length changes or artificial photoperiodic cycles (Langford et al 1999). However, Syrian Awassi rams displayed a clear seasonality of testosterone levels where the highest level was recorded in June, while the lowest was noted in December (Alomar et al 2016). In the present study, there were no significant differences (p>0.05) in mean serum testosterone level between the two experimental groups and the Control group being 6.96, 6.85 and 8.43 nmol L -1 for Control, G1 (30%) and G2 (60), respectively, with an overall mean reaching 7.41 ± 1.08 nmolL -1 , which is close to 9.46 nmol L -1 in Syrian Awassi rams at the age of 13 months using RIA technique (Zarkawi and Al-Daker, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Testosterone secretion in small ruminants was driven by natural day length changes or artificial photoperiodic cycles (Langford et al 1999). However, Syrian Awassi rams displayed a clear seasonality of testosterone levels where the highest level was recorded in June, while the lowest was noted in December (Alomar et al 2016). In the present study, there were no significant differences (p>0.05) in mean serum testosterone level between the two experimental groups and the Control group being 6.96, 6.85 and 8.43 nmol L -1 for Control, G1 (30%) and G2 (60), respectively, with an overall mean reaching 7.41 ± 1.08 nmolL -1 , which is close to 9.46 nmol L -1 in Syrian Awassi rams at the age of 13 months using RIA technique (Zarkawi and Al-Daker, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Other endogenous factors, including androgens, significantly affect the modulation of variations in the HPA axis activity (van Lier et al 2014). Alomar et al (2016) showed previously that seasonal changes of cortisol and testosterone were opposite in the Awassi rams. In addition, androgens can act directly on steroidogenic enzymes of the adrenal cortex to suppress cortisol production (Handa et al 2013).…”
Section: Cortisolmentioning
confidence: 94%
“…Other seasonal rhythms were described as well. In Syrian Awassi rams, cortisol levels were low from March to October and highest in December (Alomar et al 2016).…”
Section: Cortisolmentioning
confidence: 96%
“…Сезонность выброса кортизола после электроэякуляции наблюдали у сирийских баранов породы авасси. Кортизол достигал максимальной концентрации через 20 мин после электроэякуляции без существенной разницы между двумя сезонами (60). Обнаружено повышение уровня кортизола во время возбуждения и эякуляции, а также после электроэякуляции на анестезированных животных в рутинной практике сбора семени у мясных быков (56).…”
unclassified